THE EFFECT OF LEADERSHIP STYLE AND REWARD SYSTEM ON EMPLOYEE WELLBEING AT PDAM MANADO - Rondonuwu, Billy Imanuel; Pangemanan, Sifrid S.; Arie, Fitty Valdi (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2021)
The importance of PDAM Manado City services to meet the clean water supply needs of the Manado City community cannot be separated from the role of PDAM Manado City employees who are always required to be productive for the fulfillment of community needs. So that it cannot be separated from the Leadership Style that can encourage employee productivity and is also related to the provision of rewards or awards in order to ensure the employee wellbeing who has had a positive impact on PDAM Manado City. The purpose of this study is researcher want to investigate the effect of Leadership style and Reward System simultaneously toward the Wellbeing of PDAM Manado’s employees. This study using a quantitative method and multiple linear regression analysis as a tool to analyze the data that has been collected. Based on the result, the researcher provided several recommendations which are: Must improving and evaluating the leadership style that is carried out. The company must be able to preserve even increase the reward system.     Keywords:  Leadership style, reward system, employee wellbeing